Teleconferencing: A Viable Stress Management Delivery Mode - Hiebert, Bryan; Balshaw, Beth (Canadian Journal of Counselling and Psychotherapy, 1993)
Two sections of an upper level undergraduate course on professional stress and burnout were compared on a number of variables. One section of the course was delivered by interactive audio teleconferencing while the other section adopted a traditional on-campus classroom instructional mode. Results indicate that student academic achievement and satisfaction with the course was virtually identical for both delivery formats. Moreover, students in both delivery formats reported experiencing similar benefits from the course. There were no significant differences in the impact of the course on student stress levels, or the extent to which students applied concepts covered in the course to their personal stress management skill repertoires.